Pengaruh Model Pembelajaran Index Card Match Terhadap Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Kelas XI SMK Negeri 1 Lumut Kabupaten Tapanuli Tengah Tahun Pembelajaran 2024/2025 - Erni Yusrian Zebua; Raikhapor Raikhapor; Eduward Hottua Hutabarat; Limmarten Simatupang; Boho Parulian Pardede (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The research aims to determine the positive and significant influence of the index card match learning model on the learning motivation for Christian Religious Education and Character Education of class XI students at SMK Negeri 1 Lumut, Central Tapanuli Regency for the 2024/2025 academic year. The research hypothesis is that there is a positive and significant influence between the index card match learning model on the learning motivation of Christian Religious Education and Characteristics of class XI students at SMK Negeri 1 Lumut, Central Tapanuli Regency for the 2024/2025 academic year. Descriptive and inferential quantitative research methods. The population of all class The sample was random (random sampling) namely 25% from each class, namely 34 people. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The value rcount=0.590 which is included in the strong category>rtabel=0.339 and tcount=4.134>ttable=2.03693 shows that there is a positive and significant relationship between the index card match learning model and motivation to learn Christian Religious Education and Characteristics of class b) Regression equation. c) The determination test revealed that the magnitude of the effect was 34.81%. d) Hypothesis testing obtained Fcount=17.191>Ftable=3.32 so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the index card match learning model on the learning motivation for Christian Religious Education and Characteristics of class XI students at SMK Negeri 1 Lumut, Central Tapanuli Regency for the 2024/2025 academic year.